CIDTFF social responsibility strategy - Araújo e Sá, M. H. (coord.) (2022)
The “CIDTFF Social Responsibility Strategy” document is the result of the 4th CIDTFF Forum, entitled “Research in education and social responsibility: what are its places and possibilities within CIDTFF?“ (Investigação em educação e responsabilidade social: que lugares e possibilidades no CIDTFF?, 2020). On the basis of a shared and discussed journey, it aims, among other things, to build guidelines for a Social Responsibility (SR) strategy for CIDTFF. Based on the knowledge co-constructed around the thematic of SR in the referred Forum, the present document, targeting all CIDTFF members, intends to support Researchers in the development of practices with a sense of SR, which is transversal to the Research Agenda of CIDTFF. The CIDTFF Social Responsibility (SR) strategy defines how the Research Unit (RU) materializes this fundamental dimension of its scientific activity, through the following main vectors of action: Research, Training, Outreach (Partnerships and Cooperation) and Governance. With the implementation of this strategy, CIDTFF aims to foster more cohesive, inclusive and sustainable research and innovation processes, inspired by principles of Responsible Research and Innovation (RRI), mobilizing contributions from projects in this area2. The SR strategy foresees the involvement of multiple actors, in different ways, within research and innovation processes, as well as the framing of research questions in the context of educational issues and contemporary societal expectations, taking into account ethical aspects. It also enables greater accessibility to scientific results and the promotion of science education in integrated environments, leveraged by Science Communication initiatives.